The Kentucky Mint Julep - Nickell, Joe (Book collections on Project MUSE., 2003)
The ultimate guide to the quintessential Derby drink! A simple concoction-bourbon, mint, sugar, and water-the mint julep is legendary. Few people know its history and even fewer know how to properly mix this classic cocktail. Lighthearted, entertaining, and informative, The Kentucky Mint Julep explores the lore and legend of the Kentucky Derby's traditional tipple. Joe Nickell looks at the origins of the julep, offers a brief history of American whiskey and Kentucky bourbon, and shares some classic julep tales. Information on julep cups, tips on garnishing and serving, and reminiscences from the likes of Charles Dickens, Washington Irving, and General John Hunt Morgan give a fun, historic look at Kentucky's favorite drink. The book includes numerous recipes-for classic juleps, modern variations, non-alcoholic versions, and the author's own thoroughly researched "perfect" mint julep. This delightful book is illustrated with historic photographs, a map of the Kentucky Bourbon Trail, and more